Níveis de tireotrofina, tiroxina e resistência à insulina em obesos mórbidos eutireoideos pré e pós-cirurgia bariátrica - Gimenes, Maria Luisa Trabachin (2018)
Bariatric surgery is considered to be the most effective tool in the treatment of morbid obese, with Roux-en-Y gastric bypass or gastric bypass being the most used technique in the world, accounting for about 45% of bariatric surgeries. Weight loss results in changes in thyroid function, but these alterations are divergent among the studies. Aim: To assess the influence of weight reduction on thyroid function after 12 months of gastric bypass in patients with normal thyroid function. Methods: An observational, retrospective clinical study was performed in morbid obese euthyroid patients who underwent gastric bypass between January 2016 and July 2016. Anthropometric and laboratory data were obtained at the first visit and 12 months after bariatric surgery of 44 patients. Results: The mean age was 37.7 years of age, mean BMI before surgery of 53.9 kg/m2 and post-surgery of 35.4 kg/m2 . Mean TSH before surgery was 2.09 mIU/L and post-surgery 1.56 mIU/L, whereas preoperative free T4 was 0.89 ng/dL and postoperatively 1.04 ng/dL. In this study a mean reduction of pre-postoperative TSH of 20.3% (p <0.0001) and an average increase in free T4 pre- and postoperative of 19.0% (p <0.0001). However, there were no significant correlations between TSH and free T4. Conclusion: Weight loss 12 months after gastric bypass in morbid obese, euthyroid patients is accompanied by a significant reduction in plasma TSH levels and a significant increase in free T4 levels.